2021
DOI: 10.1186/s43044-021-00134-z
|View full text |Cite
|
Sign up to set email alerts
|

Experience with the novel unifemoral parallel sheath technique in percutaneous intervention of chronic total coronary occlusions

Abstract: Background Percutaneous interventions to address chronic coronary occlusions (CTO-PCI) often require simultaneous ipsi- and contralateral coronary injections. Although radial access is increasingly popular, bifemoral artery access is still the preferred choice of CTO operators. The aim of this case series is to demonstrate the feasibility and safety of the unifemoral parallel sheath technique, which avoids two puncture sites, increases patient comfort, and improves procedure erg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…After numerous attempts at entering the vascular graft from crossover remained unsuccessful, the right common femoral artery was punctured twice more, distally. A transfemoral parallel sheath technique has been previously described in 90 adults undergoing the treatment of chronic coronary occlusions, showing that this technique is feasible and safe in most patients [ 7 ]. We used two sheaths in a line with the second more distal than the first and showed that this approach is technically feasible in a pediatric patient with no access-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…After numerous attempts at entering the vascular graft from crossover remained unsuccessful, the right common femoral artery was punctured twice more, distally. A transfemoral parallel sheath technique has been previously described in 90 adults undergoing the treatment of chronic coronary occlusions, showing that this technique is feasible and safe in most patients [ 7 ]. We used two sheaths in a line with the second more distal than the first and showed that this approach is technically feasible in a pediatric patient with no access-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…All but 12 patients were approached via the same femoral artery employing the parallel sheath technique. 11 …”
Section: Methodsmentioning
confidence: 99%